Distinguishing Between Nile Tilapia Strains Using a Low-Density Single-Nucleotide Polymorphism Panel - Hamilton, Matthew G.; Lind, Curtis E.; Barman, Benoy K.; Velasco, Ravelina R.; Danting, Ma. Jodecel C.; Benzie, John A. H. (Frontiers in Genetics, 2020)
Nile tilapia (Oreochromis niloticus) is among the most important finfish in aquaculture, particularly in Asia. Numerous genetically improved strains of Nile tTilapia have been developed and disseminated through formal and informal channels to hatcheries, many of which operate at a relatively small scale in developing countries. The primary objective of this study was to assess the extent to which molecular genetic tools can identify different and interrelated strains of Nile tilapia in Bangladesh and the Philippines, two globally-significant producers. A tool was developed using a low-density panel of Single Nucleotide Polymorphisms (SNPs), genotyping-by-sequencing and Discriminant Analysis of Principal Components (DAPC). When applied to 2057 samples from 205 hatcheries in Bangladesh and the Philippines, for hatcheries where the hatchery-identified strain was one of the sampled core populations used to develop the tool, hatchery-identified and DAPC-assigned hatchery-level strains were in agreement in 74.1% of cases in Bangladesh and 80.6% of cases in the Philippines. Tthe dominant hatchery-identified and DAPC-assigned strains were GIFT, in Bangladesh, and GET-ExCEL –, a composite strain partially derived from GIFT –, in the Philippines.